Excellent color-matched repigmentation of human vitiligo can be obtained by mini-punch grafting using a machine in combination with ultraviolet therapy - Tomohisa Hirobe; Hisao Enami (Wolters Kluwer Medknow Publications, 2018)
A new method is reported here for treatment of vitiligo by using mini-punch grafting using a machine (mMG) in combination with ultraviolet light B (UVB) therapy. After UVB had been repeatedly irradiated to the lesional facial skin of a patient for 1 month, many mini-punch grafts were removed from the lesional skin and the same numbers of punch biopsies taken from normal scalp skin were placed into the holes of the recipient skin. Repigmentation started soon, and excellent color-matched repigmentation was observed after 12 months. Our easy and speedy mMG seems to be useful for treatment of vitiligo. Keywords: Transplantation, Melanoblast, Melanocyte, Skin, Vitiligo